EFEKTIVITAS PENERAPAN E-LEARNING SELAMA PANDEMI COVID - 19 - evalina pakpahan (PRODI AKUNTANSI FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TJUT NYAK DHIEN (UTND), 2021)
E-learning exists as a medium for distance learning. The Covid-19 pandemic creates conditions for reducing social interaction or maintaining a distance so that knowledge cannot do face-to-face. This study's results include the level of effectiveness in e-learning in the faculty of economics and business at Tjut Nyak Dhien University in the moderate category indicated by an answer index of 65.22. The discussion forum is not used correctly, and it is shown that 79 per cent of students answered disagree with the questionnaire statement. Students tend to like face-to-face lectures, as indicated by the student's answer that 59 per cent disagreed with the use of e-learning in the following semester.